2017
DOI: 10.1177/0268355517705292
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of piezoresistive sensor to PicoPress® in in-vitro interface pressure measurement

Abstract: Objective Interface pressure, the sine qua non for compression therapy, is rarely measured in clinical practice and scientific research. The goal of this study aimed to compare and examine the accuracy between a commercially available piezoresistive sensor and PicoPress® (Microlab, Padua, Italy) using the cylinder cuff model to measure in-vitro interface pressure. Method Ten piezoresistive sensors were calibrated using the National Institute of Standard and Technology certified manometer, and compared to PicoP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Chi et al 9 compared and examined the accuracy between a piezoresistive sensor and PP using the cylinder cuff model to measure in vitro interface pressure. A piezoresistive sensor might represent a viable alternative to PP in interface pressure measurement, but the standard deviation was larger for the piezoresistive sensors than PP at any given pressure, especially in the higher pressure range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chi et al 9 compared and examined the accuracy between a piezoresistive sensor and PP using the cylinder cuff model to measure in vitro interface pressure. A piezoresistive sensor might represent a viable alternative to PP in interface pressure measurement, but the standard deviation was larger for the piezoresistive sensors than PP at any given pressure, especially in the higher pressure range.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have evaluated or compared the metrological properties of these systems, particularly their accuracy. [8][9][10][11][12] Partsch and Mosti 13 compared PicoPress V R (Microlab, Padua, Italy) with Kikuhime V R (Meditrade, Soro, Denmark), and SIGaT tester V R (Ganzoni-Sigvaris, St. Gallen, Switzerland) and concluded that PicoPress was the most accurate with the least variation and error. Unfortunately, these devices' limitations make them impractical for studying change in interface pressure over several days of wearing compression bandages.…”
Section: Introductionmentioning
confidence: 99%
“…The larger the deformation, the higher the pressure. This decrease in resistance was captured by a readout circuitry consisted of an analog to digital converter, microprocessor and Bluetooth V R transmission module for data acquisition and wireless transmission to a mobile device previously described by Chi et al 5 (Figure 2). All signals were ultimately converted to pressure (mmHg).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of pressure sensing has been previously published using piezoresistive sensing principle. 4 It is a larger size device enclosed in a plastic case, 41.5x13.5 mm, and can be miniaturized and sewn into the seams of compression stockings similar to Thermotrack®.…”
Section: Methodsmentioning
confidence: 99%